The Christian ministry - Abbott, Lyman (Houghton, Mifflin and Company, 1905)
The fundamental faiths of the ministry.--The function of the ministry.--The authority of the ministry.--The individual message of the ministry.-- The social message of the ministry.--The minister as priest.--Qualifications for the ministry.--Some ministers of the olden time.-- The ministry of Jesus Christ: His methods.-- The ministry of Jesus Christ: The substance of His Teaching.